IRG1–itaconate axis in immunometabolism: mechanistic roles and therapeutic potential in inflammatory diseases - Liu, Yang; Zhang, Pengyu; Kong, Weijie; Li, Jinghui; Yang, Haoqiang; Bai, Hengqi; Fan, Gexu; Cao, Xinfang; Li, Yanjun (Frontiers in Immunology, 2026)
Cells can produce various metabolites, and both immune cells and the immune microenvironment are profoundly influenced by these metabolites. By reshaping the metabolic state of immune cells via metabolites, the host immune response can be effectively regulated, further impacting their behavior in inflammation. Itaconate, as a bypass metabolite of the tricarboxylic acid (TCA) cycle, has long been regarded as a small molecule involved in energy metabolism. However, recent studies reveal its production depends on immune response gene 1 (IRG1), which encodes aconitate decarboxylase. Under the stimulation of inflammation, the expression of IRG1 is significantly upregulated, leading to the rapid accumulation of itaconate within immune cells (especially macrophages), thus making it a key link between metabolism and immune response. Evidence indicates that macrophages are the cell type extensively synthesizing itaconate during M1 polarization driven by potent inflammatory signals (e.g., LPS stimulation). Concurrently, itaconate participates in regulating immune tolerance to cancer therapy via the transmembrane transporter SLC13A3. Under different pathological contexts the IRG1- itaconate axis exhibits distinct dynamic regulatory characteristics: During acute inflammation, itaconate limits excessive release of pro-inflammatory factors and reduces tissue damage by inhibiting succinate dehydrogenase (SDH), activating the Keap1-Nrf2 antioxidant pathway, blocking the ATF3/IκBζ-dependent pro-inflammatory program, and regulating the TET2-mediated epigenetic network. In chronic inflammation or certain tumor microenvironments, however, it may indirectly promote immunosuppression by inhibiting antigen presentation and weakening T cell cytotoxic effects. This bidirectional and environment-dependent nature makes it a key entry point for understanding the maintenance of immune homeostasis, inflammatory regulation and disease progression. This review systematically examines the production mechanisms, biochemical properties, central signaling pathways, and cross-cell effects of Itaconate as an immunomodulatory metabolite. It emphasizes its dual role in regulating inflammatory responses through multiple signaling axes and its contrasting behaviors in different disease contexts. By elucidating its molecular mechanisms, this study aims to provide novel theoretical foundations and potential therapeutic strategies for precision interventions in inflammatory diseases, while outlining future research directions and the clinical translation potential of itaconate-based approaches.